Biomechanical properties of human T cells in the process of activation based on diametric compression by micromanipulation. (February 2017) - Du, Mingming; Kalia, Neena; Frumento, Guido; Chen, Frederick; Zhang, Zhibing
Highlights: Mechanical changes of T cells in the process of activation were studied. T cell volume increased with activation. Mechanics is force-dependent, stiffness of activated cells decreased at small load. Cell mechanical strength decreased and regained when applying big force. Study facilitates development of cell sorting system based on mechanical variation. Abstract: A crucial step in enabling adoptive T cell therapy is the isolation of antigen (Ag)-specific CD8 + T lymphocytes. Mechanical changes that accompany CD8 + T lymphocyte activation and migration from circulating blood across endothelial cells into target tissue, may be used as parameters for microfluidic sorting of activated CD8 + T cells. CD8 + T cells were activated in vitro using anti-CD3 for a total of 4 days, and samples of cells were mechanically tested on day 0 prior to activation and on day 2 and 4 post-activation using a micromanipulation technique. The diameter of activated CD8 + T cells was significantly larger than resting cells suggesting that activation was accompanied by an increase in cell volume. While the Young's modulus value as determined by the force versus displacement data up to a nominal deformation of 10% decreased after activation, this may be due to the activation causing a weakening of the cell membrane and cytoskeleton. However, nominal rupture tension determined by compressing single cells to large deformations until rupture, decreased from day 0 to day 2, and then recovered on day 4 post-activation. This may be related to the mechanical properties of the cell nucleus. These novel data show unique biomechanical changes of activated CD8 + T cells which may be further exploited for the development of new microfluidic cell separation systems.